Intracranial pressure and mean arterial pressure monitoring in freely moving rats via telemetry; pilot study - Kozler, Petr; Maresova, Dana; Pokorny, Jaroslav (Neuro-endocrinology letters, 2019)
OBJECTIVES: Accurate values of the intracranial pressure (ICP) and mean arterial pressure (MAP) are the prerequisite for calculating cerebral perfusion pressure (CPP). Increased ICP values decrease CPP. The origin of ICP increase in the clinical cases after brain ischemia and diffuse brain injury is the cellular brain edema (CE). Short-term monitoring of ICP and MAP is possible only in the unconscious patients, in experiments with rats it used to be possible only in general anesthesia. Long-term monitoring of ICP or MAP in the clinical practice is not possible. We therefore introduce an experimental model with telemetric monitoring. METHODS: ICP (subdurally) and MAP (intracarotically) were monitored in freely moving rats for 72 hours by DSI™ (Data Sciences International) telemetry system. The control group consisted of 8 rats, the experimental group had 8 animals with CE-induced by water intoxication. RESULTS: The mean MAP, ICP and CPP values were significantly higher in the experimental group. Average values of MAP were 19.9 mmHg (18%), ICP 5.3 mmHg (55%), CPP 14.5 mmHg (15% higher). CONCLUSION: The results of the pilot study verified possibilities of long-term telemetric monitoring of the mean arterial and intracranial pressures for the determination of current cerebral perfusion pressure in freely moving rats under physiological conditions and with increased intracranial pressure due to the induced cerebral edema. Detailed analysis of the course of the curves in the experimental group revealed episodes of short-term CPP reduction below the optimum value of 70 mmHg. Interpretation of these episodes requires simultaneous monitoring of rat behavior.
Keywords: telemetrie; Animals; Cerebrovascular Circulation; mozkový krevní oběh; Monitoring, Ambulatory; Pilot Projects; Brain Edema; pilotní projekty; technologie dálkového snímání; Intracranial Pressure; intrakraniální tlak; Telemetry; edém mozku; ambulantní monitorování; krysa rodu Rattus; Remote Sensing Technology; Arterial Pressure; zvířata; arteriální tlak; Rats